Intact Fish Skin Graft vs. Standard of Care in Patients with Neuroischaemic Diabetic Foot Ulcers (KereFish Study): An International, Multicentre, Double-Blind, Randomised, Controlled Trial Study Design and Rationale - Dardari, Dured; Potier, Louis; Sultan, Ariane; Francois, Maude; M’Bemba, Jocelyne; Bouillet, Benjamin; Chaillous, Lucy; Kessler, Laurence; Carlier, Aurelie; Jalek, Abdulkader; Sbaa, Ayoub; Orlando, Laurent; et al. (Medicina (Kaunas, Lithuania), 2022)
Background: Cell and/or tissue-based wound care products have slowly advanced in the treatment of non-healing ulcers, however, few studies have evaluated the effectiveness of these devices in the management of severe diabetic foot ulcers. Method: This study (KereFish) is part of a multi-national, multi-centre, randomised, controlled clinical investigation (Odin) with patients suffering from deep diabetic wounds, allowing peripheral artery disease as evaluated by an ankle brachial index equal or higher than 0.6. The study has parallel treatment groups: Group 1 treatment with Kerecis® Omega3 Wound™ versus Group 2 treatment with standard of care. The primary objective is to test the hypothesis that a larger number of severe diabetic ulcers and amputation wounds, including those with moderate arterial disease, will heal in 16 weeks when treated with Kerecis® Omega3 Wound™ than with standard of care. Conclusion: This study has received the ethics committee approval of each participating country. Inclusion of participants began in March 2020 and ended in July 2022. The first results will be presented in March 2023. The study is registered in ClinicalTrials.gov as Identifier: NCT04537520.